2022
DOI: 10.3389/fneur.2022.964197
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection in neurodegenerations of the brain and eye: Lessons from the past and directions for the future

Abstract: BackgroundNeurological and ophthalmological neurodegenerative diseases in large part share underlying biology and pathophysiology. Despite extensive preclinical research on neuroprotection that in many cases bridges and unifies both fields, only a handful of neuroprotective therapies have succeeded clinically in either.Main bodyUnderstanding the commonalities among brain and neuroretinal neurodegenerations can help develop innovative ways to improve translational success in neuroprotection research and emergin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 128 publications
0
13
0
Order By: Relevance
“…Alternatively, these observations may parallel the atypical intrinsic hyperactivity observed in degenerating/remodeling rd1 mice retinas, which is thought to arise from remnant photoreceptors and bipolar cells, with activity (and modulation) by horizontal and amacrine cells ( Borowska et al, 2011 ; Haq et al, 2014 ). Sustained activity, even in an aberrant form, has the potential to facilitate retinal neuron regeneration ( Corredor and Goldberg, 2009 ; Lim et al, 2016 ; Levin et al, 2022 ), and we have shown that in zebrafish, surviving photoreceptors facilitate functional recovery following cytotoxic damage ( Sherpa et al, 2014 ). Thirdly, an additional consideration for interpreting the recovery of function within the regenerating zebrafish retina is the restoration and/or remodeling of inhibitory interneuron inputs, including horizontal cells in the outer retina.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, these observations may parallel the atypical intrinsic hyperactivity observed in degenerating/remodeling rd1 mice retinas, which is thought to arise from remnant photoreceptors and bipolar cells, with activity (and modulation) by horizontal and amacrine cells ( Borowska et al, 2011 ; Haq et al, 2014 ). Sustained activity, even in an aberrant form, has the potential to facilitate retinal neuron regeneration ( Corredor and Goldberg, 2009 ; Lim et al, 2016 ; Levin et al, 2022 ), and we have shown that in zebrafish, surviving photoreceptors facilitate functional recovery following cytotoxic damage ( Sherpa et al, 2014 ). Thirdly, an additional consideration for interpreting the recovery of function within the regenerating zebrafish retina is the restoration and/or remodeling of inhibitory interneuron inputs, including horizontal cells in the outer retina.…”
Section: Discussionmentioning
confidence: 99%
“…Given recent advances in our understanding of the mechanisms of RGC death, a variety of novel approaches for glaucoma neuroprotection are being investigated 9 , 10 . One main challenge for the development of these IOP-independent neuroprotective therapies is the lack of glaucoma progression endpoints that could be tested in clinical trials of relatively short duration in a glaucoma population treated with concomitant IOP-lowering therapies.…”
Section: Introductionmentioning
confidence: 99%
“…The deprivation of these factors resulting from the blockage in retrograde axonal transport to the RGC soma as well as their degradation due to increased ROS levels may trigger apoptosis in RGCs [ 16 , 17 ]. Treatment using these neurotrophic factors have demonstrated protection of RGCs in varying experimental models of injury [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%